Handbook of self assembled semiconductor nanostructures for novel devices in photonics and electronics - Henini, Mohamed (Elsevier, 2008)
In 1969, Leo Esaki and Ray Tsu from IBM, USA, proposed research on and#39;man-made crystalsand#39; using a semiconductor superlattice (a semiconductor structure comprising alternating ultra-thin layers of semiconductor materials with different properties). This was perhaps the first proposal to advocate the engineering of a new semiconductor material.